The Ease Of Use And Discount Toward Purchase Decisions And Customer Satisfaction On E-Ticketing In Indonesia - Edhie Budi Setiawan; Nadhila Cory Sabrina; Aulia Mutia Alda; Dian Artanti Arubusman; Amrulloh Ibnu Kholdun (STIE Amkop Makassar, 2024)
Ease of use and discounts are efforts that can be made by Tiket.com to improve customer decisions and satisfaction in purchasing airline tickets. This research aims to find out the effect of ease of use and discounts on purchasing decisions and customer satisfaction. The research method used is quantitative by disseminating questionnaires to 130 respondents. Respondents in this study were taken by purposive sampling. The data obtained is processed using SEM-PLS. The results of this study showed a significant and significant relationship between ease of use and discounts to purchasing decisions and customer satisfaction. Therefore, the higher the ease of use and discounts, the higher the purchase decision and the increased customer satisfaction in buying flight tickets in Tiket.com.